THE IMPACT OF PROFITABILITY, LIQUIDITY, AND GOOD CORPORATE GOVERNANCE ON FINANCIAL DISTRESS WITH CAPITAL STRUCTURE AS A MODERATION VARIABLE - Wijayanti, Eka; Fitriyah, Fitriyah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Financial distress is a situation when a company’s operating cash flows are insufficient to meet its obligations and the company is required to take corrective action. The aim of this study is to know the impact of profitability, liquidity, GCG on financial distress with capital structure as a variable of moderation. The population in this study amounted to 82 companies in the property and real estate sector listed in the EIB period 2017-2021. The sampling technique used is purposive sampler and produces as many as 25 companies. The results of the research showed that profitability has a significant positive impact on financial distress, liquidity has a significant positive effect on financial disaster, GCG has a substantial negative impact on finance distress. Capital structure as a variable of moderation can’t strengthen the relationship of profitability to financial distress, capital structure can weaken the relationship between liquidity to financial crisis, and capital structure cannot strengthen relationship between GCG and financial crisis.